Pemanfaatan Sampah Organik dan Anorganik dalam Upaya Pengelolaan Sampah di Desa Besuki, Situbondo - Najmudil Akbar Kadafi; Satya Jati Pratama; Zein Salman Syaifulloh; Hafizh Vretama Iqbar Hidayat; Dendya Bagus Irawan; Hoky Tegar Sugihartanto; Ratna Endang Widuatie (Universitas 45 Surabaya, 2023)
Besuki Village is one of the villages with an average community whose livelihood is in the trade sector, thus household waste production is a major problem in the village. The purpose of this kkn program is to utilize organic and inorganic waste to reduce the amount of waste in Besuki village by applying education to the community about the types of waste and the utilization that can be done. The method used in this work program is by conducting counseling and practice / utilization. The counseling and utilization carried out produced organic waste products, namely solid compost and liquid compost (POC) and inorganic waste products, namely ecobricks. With the counseling and practice of waste utilization, it is expected that composting will be applied to the garden and TOGA garden in Besuki Village, and environmental cadres in the village can make ecobricks which can later be used to decorate and make useful items in Besuki Village.